Administrative information system for customer service and inventory of CV PARVIFE Decor using Visual Basic.NET - Parcel Natalnael Hutabarat; Eko Hadiyanto (Jurnal Sistem Informasi, 2010)
We make customer service and administration system proposed inventory on this design, it can replace the manual system to process customer service and inventory administration, sehindiharapkan can overcome the weaknesses that have been faced by CV Parvife Decor is also a way to facilitate activities during This has many disadvantages. With the system that uses computer services is expected to help the administration and customer service and inventory of CV Parvife Decor.